The Impact of CSR, Capital Intensity, Inventory Intensity, and Intangible Assets on Tax Aggressiveness - Suryarini, Trisni; Hajawiyah, Ain; Munawaroh, Siti (Jurnal Dinamika Akuntansi, 2021)
Purpose: The purpose of this study is to determine whether tax aggressiveness is influenced by CSR, capital intensity, inventory intensity, and intangible assets.Method: The sample was selected using a purposive samplings technique with the result of 61-unit analysis consist of transportation companies listed on the Indonesia Stock Exchange from 2016 to2019. The analysis method used in this research is multiple regression analysis.Finding: The study finds that CSR disclosure has a significant positive effect on tax aggressiveness, while capital intensity and inventory intensity have no effect on tax aggressiveness. In addition, in- tangible assets have a significant negative effect on tax aggressiveness.Novelty: This study examines the effect of CSR disclosure, capital intensity, inventory intensity, and intangible asset on tax aggressiveness in transportation company period 2016-2019. The previous study only examines those variables separately and focuses on different samples and different periods.